First Histopathological and Molecular Characterization of Giant Thorny-headed Worm, Macracanthorhynchus hirudinaceus (Pallas, 1781) (Acanthocephala: Oligacanthorhynchidae) in Wild Boars, Sus scrofa Linnaeus, 1758 from Eastern Türkiye - Celik, Figen; Kilinc, Seyma Gunyakti; Ceribasi, Songul; Kesik, Harun Kaya; Simsek, Sami (Springer Int Publ Ag, 2024)
Background Macracanthorhynchus hirudinaceus (Pallas, 1781) is a zoonotic acanthocephalan that parasitizes the small intestine of wild boars. It is a pathogenic that causes economic losses, and poses a public health threat due to increased emergence. Purpose The aims of this study is describes histopathologically the damage caused by M. hirudinaceus in the small intestine of wild boar Sus scrofa Linnaeus, 1758, and molecularly characterize this parasite (sequences, haplotypes, phylogeny) for the first time in Elazig city, T & uuml;rkiye. Results A high prevalence of infection was obtained. Upon separating the worms, it was discovered that there were ulcers resembling craters in the center, of the small intestine mucosa, surrounded by edema. The intestine wall where the parasite attached was damaged, with the villi epithelium and lamina propria in the mucosa being destroyed. The genomic DNA was isolated from all M. hirudinaceus samples, and PCR amplified the 489 bp gene fragments were sequenced and confirmed that all 21 sequences were M. hirudinaceus. The haplotype analysis of the sequences revealed the presence of a central star-shaped haplotype, in addition to four other haplotypes. Conclusion After conducting sequence analysis, the genetic differences between the M. hirudinaceus sequences obtained in this study and those reported from Europe and Japan suggest that this parasite is endemic to T & uuml;rkiye's local wild boar population. Also, four haplotypes were identified, distinguishing it from other haplotypes by 1-5 mutation steps. It is essential to consider the worm's sequences and the formation of haplotypes, since these intrinsic characteristics may impact in the epidemiology and pathology of the worm in the future.
Keywords: Macracanthorhynchus hirudinaceus; Wild boar; Sequence; Haplotype